A Proinflammatory Immune Response Might Determine Toxoplasma gondii Vertical Transmission and Severity of Clinical Features in Congenitally Infected Newborns - Gómez-Chávez, Fernando; Cañedo-Solares, Irma; Ortiz-Alegría, Luz Belinda; Flores-García, Yevel; Figueroa-Damián, Ricardo; Luna-Pastén, Héctor; Gómez-Toscano, Valeria; López-Candiani, Carlos; Arce-Estrada, G. Emmanuel; Bonilla-Ríos, Christian A.; Mora-González, Juan Carlos; García-Ruiz, Ricardo; et al. (Frontiers in Immunology, 2020)
Toxoplasma gondii is the etiological agent of toxoplasmosis. Mother to child transmission of this parasite can occur during pregnancy. Newborns with congenital toxoplasmosis may develop central nervous system impairment, with severity ranging from subclinical manifestations to death. A pro-inflammatory/regulated specific immune profile is crucial in the defense against the parasite; nevertheless, its role in the infected pregnant women and the congenitally infected offspring has been poorly explored, and there is still no consensus about its relation to parasite vertical transmission, nor to severity and dissemination in the congenitally infected newborns. This work aimed to characterize these relations by means of principal component and principal factor analyses. For this purpose, we determined the specific production of the four IgG antibody subclasses, cytokines and lymphocyte proliferation in the T. gondii infected pregnant women -ten who transmitted the infection to their offspring and seven who did not- as well as in eleven newborns congenitally infected and grouped according to disease severity (five mild and six moderate/severe) and dissemination (four local and seven disseminated). We found that the immune response of non-transmitter women differed to that of the transmitters, the later having a stronger pro-inflammatory response, supporting a previous report. We also found that newborns who developed moderate/severe disease presented higher levels of lymphocyte proliferation, particularly of CD8+ and CD19+ cells, a high proportion of TNF-α producers, and reduced expression of the immune modulator TGF-β, as opposed to children who developed mild clinical complications. Our results suggest that a distinctive not regulated pro-inflammatory immune response might favor T. gondii vertical transmission and the development of severe clinical manifestations in congenitally infected newborns.